2018
DOI: 10.1007/s00442-018-4257-5
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of cyanobacterial carbon to a higher trophic-level fish community in a eutrophic lake food web: fatty acid and stable isotope analyses

Abstract: The dietary utilization of cyanobacterial carbon by fish communities is poorly understood. We examined the transfer of cyanobacterial carbon to fish in a eutrophic lake using fatty acid biomarkers and measuring the stable carbon isotope ratios of fatty acid and bulk nitrogen. We collected five species of fish (Hypomesus nipponensis, Carassius sp., Cyprinus carpio, Tridentiger brevispinis, and Gymnogobius castaneus) as well as the seston from June to November 2016 from Lake Hachiro, Japan. Cyanobacterial blooms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…On the contrary, for 18:3ω3, the expected isotopic fractionation of epilithic biofilm to S. leucomaenis via aquatic insects was 1.6–8.0‰. Fujibayashi et al [29] found no significant difference of isotopic value of 18:3ω3 between freshwater fish and blooming cyanobacteria. However, the mechanism of this inconsistent and variable fractionation for 18:3ω3 was not explainable in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the contrary, for 18:3ω3, the expected isotopic fractionation of epilithic biofilm to S. leucomaenis via aquatic insects was 1.6–8.0‰. Fujibayashi et al [29] found no significant difference of isotopic value of 18:3ω3 between freshwater fish and blooming cyanobacteria. However, the mechanism of this inconsistent and variable fractionation for 18:3ω3 was not explainable in this study.…”
Section: Discussionmentioning
confidence: 99%
“…; Supelco, Inc., Bellefonte, PA, USA). The operating conditions were as described by Fujibayashi et al [29]. Each essential fatty acid peak was identified as described above for the GC-FID analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipids and fatty acids (FA) are important biochemical components of aquatic food webs and access to food sources with specific FA profiles helps ensure high quality nutrition is available to support metabolic processes that can influence consumer fitness (Arts et al., 2001; Swanson et al., 2012). Research to date on the FA of river food webs has largely been focused on temperate regions (Fujibayashi et al., 2018; Twining et al., 2017). Few studies have reported on FA of freshwater food webs in the tropics with the majority of existing tropical freshwater FA studies coming from African lakes (Hecky et al., 2010; Kwetegyeka et al., 2008; Zenebe et al., 1998).…”
Section: Introductionmentioning
confidence: 99%